Characteristics of high yielding cassava varieties - Cock, James H. (Cambridge University Press, 1976)
Forty different cultivars of cassava were grown in unreplicated plots at a plant population of 20,000 plants/ha in fertile soil. Harvests were taken at 4, 6, 8, 10 and 12 mo after planting 18 varieties. The characteristics of the 2 highest yielding varieties, M Colombia 113 (66 tons/ha) and M Colombia 22 (32 tons/ha), were compared with the other types. M Colombia 22 is an early maturing type (25 tons/ha after 6 months) with a very high harvest index; M Colombia113 yields little better than average 6 mo after planting. High yield is associated with a balance between leaf and root production, so that leaf area index does not decline excessively in the later growth stages. Changing canopy structure is unlikely to increase yields. (AS)